2014
DOI: 10.1371/journal.pone.0115463
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle Optimization for Panic Flow - Reducing the Tangential Momentum Increases the Escape Speed

Abstract: A disastrous form of pedestrian behavior is a stampede occurring in an event involving a large crowd in a panic situation. To deal with such stampedes, the possibility to increase the outflow by suitably placing a pillar or some other shaped obstacles in front of the exit has been demonstrated. We present a social force based genetic algorithm to optimize the best design of architectural entities to deal with large crowds. Unlike existing literature, our simulation results indicate that appropriately placing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Notably, it has been experimentally proved for granular matter discharged from a silo [29,30], and the passage of different animals (such as sheep [13,31] and mice [32]) through narrow doors. Nevertheless, apart from some inconclusive results [3,[33][34][35], an experimental confirmation of this feature in real pedestrian tests is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it has been experimentally proved for granular matter discharged from a silo [29,30], and the passage of different animals (such as sheep [13,31] and mice [32]) through narrow doors. Nevertheless, apart from some inconclusive results [3,[33][34][35], an experimental confirmation of this feature in real pedestrian tests is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Frank et al (2011) studied the influence of diverse distance between panel-like obstacle and exit, and showed that an obstacle could not guarantee better chance of survival. Jiang et al (2014) carried out an experiment to validate simulated optimal obstacle layout, demonstrating that two pillars on both sides of the exit minimized the escape time.…”
Section: Introductionmentioning
confidence: 99%
“…Most related to our work is the optimization of crowd‐affecting environment parameters. Optimization of features, such as pillars, has been studied by Rodriquez et al and Jiang et al for a single steering algorithm. Recent literature shows that the choice of steering algorithm affects the output of environment optimizations …”
Section: Related Workmentioning
confidence: 99%